Role of oral hyaluronic acid for joint health: insights from rat models and clinical trials - Wang, Botao; Wang, Fengli; Zhang, Tianmeng; Bai, Junying; Cui, Shumao; Shi, Haining (Frontiers in Nutrition, 2025)
BackgroundEarly studies have demonstrated the significant potential of hyaluronic acid (HA) in alleviating osteoarthritis (OA); however, the relationship between different molecular weights (MWs) and efficacy remains unclear.MethodsThe rat model was used to evaluate the effects of different MWs of HA on OA and to identify the MW that was most effective in alleviating OA. Based on this, a clinical trial was conducted to verify the selected HA’s clinical efficacy.ResultsThe results showed that HA significantly reduced joint swelling in rats, dramatically increased HA content in the serum and joint synovial fluid, decreased serum and joint synovial fluid levels of pro-inflammatory cytokines, and reduced the expression of matrix metalloproteinases (MMPs), inducible nitric oxide synthase (iNOS), and cyclooxygenase-2 (COX-2) when compared with the OA group, especially high-MW HA. Importantly, these protective roles may be attributed to the immune regulation of HA. Clinical trial results indicated that HA significantly decreased pain, stiffness, and physical function of Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores and had no significant impact on blood and urine indices.ConclusionOur findings suggest that oral supplementation with HA can reduce the progression of arthritis, pain, and cartilage damage, and can be a new strategy to relieve joint discomfort.